Miskonsepsi Guru Matematika SMP pada Operasi Pengurangan Bilangan Bulat dan Solusinya - Darmawan, Puguh; Prastiwi, Laras Shita (Jurnal Pendidikan dan Teknologi Pembelajaran Matematika, 2025)
This study examines the misconceptions of middle school mathematics teachers regarding the concept of integer subtraction operations and their solutions. The study employs three instruments with different integer subtraction expressions. A qualitative approach with a case study design is used in this research. The research subjects are middle school teachers, and the data consists of the subjects' written responses. The data analysis technique employed in this study is interactive data analysis. The results indicate that the subjects experience misconceptions regarding number signs and operation signs. The subjects mistakenly assume that number signs can be operated on together with operation signs. The researcher recommends that middle school teachers use simple illustrations to explore the concept of integer subtraction operations.